Delivery of full predicted energy from nutrition and the effect on mortality in critically ill adults: A systematic review and meta-analysis of randomised controlled trials. Issue 6 (December 2018) - Ridley, Emma J.; Davies, Andrew R.; Hodgson, Carol L.; Deane, Adam; Bailey, Michael; Cooper, D. Jamie
Summary: Background: The amount of energy required to improve clinical outcomes in critically ill adults is unknown. Objective: The aim of this systematic review and meta-analysis was to evaluate the impact of near target energy delivery to critically ill adults on mortality and other clinically relevant outcomes. Design: Following PRISMA guidelines, MEDLINE, EMBASE, CINHAL and the Cochrane Library were searched for randomised controlled trials evaluating nutrition interventions in adult critical care populations. Included studies compared delivery of ≥80% of predicted energy requirements (near target) from enteral and/or parenteral nutrition to <80% (standard care) and reported mortality. The quality of individual studies was assessed using the Cochrane 'Risk of Bias' tool, and the overall body of evidence using the GRADE approach. Fixed or random effect meta-analyses were used pending the presence of heterogeneity (I 2  > 50%) when 3 or more studies reported the same outcome. Outcomes are presented as risk ratio (RR), 95% confidence interval (CI). Results: Ten trials with 3155 participants were included. Mortality was unaffected by the intervention (RR 1.02, 95% CI 0.81, 1.27, p = 0.89, I 2  = 25%). Evaluation of studies of higher quality and low risk of bias did not alter the mortality inference (3 trials, 352 participants, RR 0.83, 95% CI 0.49, 1.40, p = 0.19, I 2  = 39%). The quality of evidence across outcomes was very low. Conclusions: The delivery of near target energy when compared to standard care in adult critically ill patients was not associated with an effect on mortality. Because the quality of the evidence across outcomes was very low there is considerable uncertainty surrounding this estimate. This has implications for clinical utility of the evidence within the included reviews.